Case series of BRAF‐mutated advanced melanoma treated with encorafenib plus binimetinib combination therapy. Issue 3 (11th November 2020) - Fujimura, Taku; Yoshino, Koji; Kato, Hiroshi; Fujisawa, Yasuhiro; Nakamura, Yoshiyuki; Yamamoto, Yuki; Kunimoto, Kayo; Ito, Takamichi; Matsushita, Shigeto; Maekawa, Takeo; Ohuchi, Kentaro; Amagai, Ryo; et al.
Abstract: The efficacy of encorafenib plus binimetinib (E + B) combination therapy for BRAF ‐mutated advanced melanoma as second‐line therapy and beyond is still unknown. In this report, we investigated 22 cases of BRAF ‐mutated advanced melanoma treated with E + B combination therapy. The objective response rate (ORR) for the total cohort was 68.4%. Notably, the ORR for the second‐line and beyond cohort was 73.3%, suggesting that the therapeutic effect of E + B combination therapy is comparable with that of first‐line targeted therapy. In contrast, overall survival and progress‐free survival in our present cohort was worse than that in a previous clinical trial. Notably, although the incidence rate of severe adverse events was higher than that in a previous report, our present study suggested that E + B combination therapy is a well‐tolerated antimelanoma regimen. Our present study suggested that the efficacy and safety profile of E + B combination therapy as a second‐line therapy and beyond is comparable with that of first‐line targeted therapy.